Do preconceito à expertise: percepção de suspeitos em abordagens policiais - Guilherme Fernando Soares de Araújo (2017)
This dissertation aims to analyze the complexity of decision-making and the trial of military police of the 26th battalion of Police of Minas Gerais, making use of your discretion in police action of police approach. In this way, the overall objective will be to show the variables and factors associated with this "power", through observation and autoconfrontações in the field. The specific objectives can be delineated into four: 1) understanding the process approach, picking up other perspectives, enlarging the cases in which the discretion would bring trials in situation to identify suspects and protect the team; 2nd) investigate what influence the judgments and perceptions cops in approach; 3rd) to investigate the decision-making process and trial, and 4) propose improvements in the structuring of teams and in training at battalion studied. All the text will bring about the following problem analysis: what's the difference between abuse of force necessary? What if you've noticed is that most of the decisions and judgments taken are based on skills, arising from perceptions that are created between the officer and the suspect's behavior, result suitable coupling agent experiences with the situation found. The key point of skill are the experiences and experiences accumulated in different situations. The officer uses the strategy of detecting traces of suspicion by adjusting every occurrence, producing inclusions and exclusions of possibilities. Soon, all the skill in detection is on; depends on the context and the suspect. The competence depends primarily on the situation and practice (the ability of the body entwined the rules), and this is not acquired through representations, it is only in this situation and for the selection and police action may result in the development of effective and proportionate action.